2010
DOI: 10.1007/s10620-010-1480-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Expression in Mice of a Transgene Containing 3.3 kb of the Human Lactase-Phlorizin Hydrolase (LPH) 5′ Flanking Sequence

Abstract: Background and Aim-The regulation of human intestinal lactase-phlorizin hydrolase remains incompletely understood. One kb of pig and 2 kb of rat 5′-flanking sequence controls correct tissue, cell, topographic, and villus LCT expression. To gain insight into human LCT expression, transgenic mouse lines were generated from 3.3 kb of human LPH 5′ flanking sequence from a lactase persistent individual fused to a human growth hormone (hGH) reporter bounded by an insulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Using an unbiased epigenome-wide approach verified by targeted pyrosequencing, we have identified position cg20242066 (chr2: 136595261; hg19) as differentially methylated in the jejunum of lactase persistent and lactase non-persistent children and adolescents. This CpG is located in the region essential for spatio-temporal regulation of human LCT expression, which has been previously demonstrated by introducing a construct containing the sequence 3.3kbs upstream of the TSS in transgenic mice 39 . Linear regression analysis showed that DNA methylation at both the LCT promoter and enhancer is largely impacted by genotype at −13910C > T, with CC homozygotes having the highest, and TT homozygous individuals the lowest methylation levels.…”
Section: Discussionmentioning
confidence: 79%
“…Using an unbiased epigenome-wide approach verified by targeted pyrosequencing, we have identified position cg20242066 (chr2: 136595261; hg19) as differentially methylated in the jejunum of lactase persistent and lactase non-persistent children and adolescents. This CpG is located in the region essential for spatio-temporal regulation of human LCT expression, which has been previously demonstrated by introducing a construct containing the sequence 3.3kbs upstream of the TSS in transgenic mice 39 . Linear regression analysis showed that DNA methylation at both the LCT promoter and enhancer is largely impacted by genotype at −13910C > T, with CC homozygotes having the highest, and TT homozygous individuals the lowest methylation levels.…”
Section: Discussionmentioning
confidence: 79%